Comparison of tissue reaction in primary tracheal repair using silk, monofilament absorbable (Polyglecaprone), and multifilament absorbable (Polyglactin 910) sutures (An experimental study on New Zealand rabbits) - Santi, Santi; Wibowo, Marjono Dwi (Edelweiss Applied Science and Technology, 2025)
Surgical interventions for tracheal trauma include repairing lacerations, reducing and closing cartilage fractures, and performing end-to-end anastomosis in cases of complete transection. One of the potential long-term complications following tracheal surgery is tracheal stenosis. The inflammatory reaction depends on the suture material used, the type of tissue being sutured, and the immune system. Several factors related to the suture material that influence the inflammatory reaction include suture absorbability, the number of filaments, suture size, and tissue reactivity to the suture. This study aimed to compare the inflammatory reaction (tissue reaction) caused by various suture materials in primary tracheal repair in male New Zealand rabbits. This experimental study employed a randomized controlled trial design, conducted on male New Zealand white rabbits. The rabbits were acclimatized for seven days, followed by permuted block randomization, dividing the samples into four groups. After the inflammatory phase (7 days), tissue reactions in the surgical area were examined post-tracheal reconstruction. Data analysis was performed using SPSS software. Each group consisted of six samples, demonstrating homogeneity in terms of age (p = 0.93), preoperative weight (p = 0.87), and postoperative weight (p = 0.88). Macroscopic evaluation showed no wound dehiscence, pus, or tracheal defects caused by suture displacement. Histopathological analysis revealed a significantly different degree of inflammation (p = 0.049) between the two treatment groups. Monofilament absorbable sutures (polyglecaprone) exhibited a lower inflammatory reaction than multifilament absorbable sutures (polyglactin 910) in primary tracheal repair, with silk sutures as the control.